2021
DOI: 10.21585/ijcses.v5i1.126
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Eighth Grade Students' Domain-General Computational Thinking Skills

Abstract: The aim of this study was to examine the domain-general CT skills of 8th grade students in Turkey. In the study, first, the domain-general CT scale was adapted to Turkish and then, the CT skills of the students were examined. This survey research was conducted with the 284 eighth grade students. The data were analyzed through confirmatory factor analysis, independent sample t-test and Pearson correlation test. The results of the validity and reliability tests showed that the domain-general CT scale was suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This may indicate that the Hum-student group was more perceptually influenced in the learning process during the AI course in terms of visual programming. In addition, Karalar and Alpaslan (2021) indicated that students with more experience in programming have higher computational thinking skills than those with no programming experience. The Sci-student group had more programming experience, and the Hum-student group had less, but the findings were not consistent with those of previous studies ( Karalar and Alpaslan, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that the Hum-student group was more perceptually influenced in the learning process during the AI course in terms of visual programming. In addition, Karalar and Alpaslan (2021) indicated that students with more experience in programming have higher computational thinking skills than those with no programming experience. The Sci-student group had more programming experience, and the Hum-student group had less, but the findings were not consistent with those of previous studies ( Karalar and Alpaslan, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Karalar and Alpaslan (2021) indicated that students with more experience in programming have higher computational thinking skills than those with no programming experience. The Sci-student group had more programming experience, and the Hum-student group had less, but the findings were not consistent with those of previous studies ( Karalar and Alpaslan, 2021 ). This was because the students manipulated the visual programming block learning process (e.g., modeling), which made it possible for them to repeat computational thinking patterns that would enhance their computational thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…There are several reasons for developing a new bid scale for pre-service teachers. The age groups of the CT scales developed in Turkey are at the middle school or high school level (Gülbahar et al, 2018;Yağcı, 2019;Kukul & Karataş, 2019;Karalar & Alpaslan, 2021). In the scales developed for teachers (Korkmaz et al, 2017;Dolmacı & Akhan, 2020), the current bid scale was needed because the subject content such as creativity, critical thinking, and collaborative work within the scope of the subject is not encountered in the international literature.…”
Section: Why Was a New Scale Needed?mentioning
confidence: 99%